Principles and Pedagogies in Jewish Education - Chazan, Barry (Springer International Publishing : Imprint: Palgrave Macmillan, 2022)
This book is aimed at Improving contemporary educational practice by rooting it in clear analytical thinking. The book utilizes the analytic approach to philosophy of education to elucidate the meaning of the terms: 'education'; 'moral education; 'indoctrination"; ;''contemporary American Jewish education''; 'informal Jewish education"; ''the Israel experience'; and" Israel education". The final chapter of the book presents an educator's credo for 21st-century Jewish education and general education. Barry Chazan is Professor Emeritus of the Hebrew University of Jerusalem and Research Professor at the George Washington University Graduate School of Education and Human Development.